Shine & Lal index as a predictor for early detection of β-thalassemia carriers in a limited resource area in Bandung, Indonesia - Ani Melani Maskoen; Lelani Reniarti; Edhyana Sahiratmadja; Joice Sisca; Sjarif Hidajat Effendi (BMC, 2019)
Abstracts Background Thalassemia is the most common inherited disease in the world, involving α- or β-globin in red blood cells. Thalassemia cases rank fifth in the list of national catastrophic diseases in Indonesia; however, nationwide screening for thalassemia carriers is not yet mandatory. This study aimed to assess whether blood count metrics, such as the Shine & Lal index (SLI; MCV*MCV*MCH/100), might serve as a predictor to screen thalassemia carriers in a limited resource area where molecular methods are not readily available. Methods During a family gathering of thalassemia patients, family members (n196) underwent a complete blood count test. Those with MCV < 80 fL and/or MCH < 27 pg and/or SLI < 1530 were further examined for Hb analysis. Only samples with HbA2 fraction > 4% or with a peak in the HbE fraction were sequenced to confirm β-globin gene mutations. Results Of 196 family members, 117 (59.6%) had low MCV and/or low MCH and/or low SLI. The HbE fraction (mean 24.06% ± 0.95, range 22.4-26.5) was found in 27 (13.7%) cases, and all had a mutation at codon (CD)26 (c.79G > A). The mean HbA2 fraction in these samples was 3.18% ± 0.62 (range 2.6-3.8). For samples with HbA2 > 4% (n30; 15.3%), all had mutations at IVS1nt5 (c.92 + 5 G > C; n28), CD8/9 (c.27_28insG; n1) and CD19 (c.59A > G; n1). The mean HbA2 fraction with a mutation at IVS1nt5 (c.92 + 5 G > C) was 4.65% ± 0.77 (range 4.0-5.6). Interestingly, anaemia was only present in 25 and 57% of β-thalassemia carriers with mutations at CD26 (c.79G > A) and at IVS1nt5 (c.92 + 5 G > C), respectively. Conclusions The Shine & Lal index is helpful in the early screening of β-thalassemia carriers, since this index confirms mutations at CD-26 (c.79G > A) and at IVS1nt5 (c.92 + 5 G > C), which are both common mutations in Bandung, Indonesia. Further DNA analysis is a topic of interest to map variants in globin genes and their distribution across populations.